Development and introduction of inactivated poliovirus vaccines derived from Sabin strains in Japan - Shimizu, Hiroyuki (Vaccine, 2016)
During the endgame of global polio eradication, the universal introduction of inactivated poliovirus vaccines is urgently required to reduce the risk of vaccine-associated paralytic poliomyelitis and polio outbreaks due to wild and vaccine-derived polioviruses. In particular, the development of inactivated poliovirus vaccines (IPVs) derived from the attenuated Sabin strains is considered to be a highly favorable option for the production of novel IPV that reduce the risk of facility-acquired transmission of poliovirus to the communities. In Japan, Sabin-derived IPVs (sIPVs) have been developed and introduced for routine immunization in November 2012. They are the first licensed sIPVs in the world. Consequently, trivalent oral poliovirus vaccine was used for polio control in Japan for more than half a century but has now been removed from the list of vaccines licensed for routine immunization. This paper reviews the development, introduction, characterization, and global status of IPV derived from attenuated Sabin strains.